IMPACT OF URBANIZATION ON MICROBIOLOGICAL SAFETY: COMPREHENSIVE ASSESSMENT AND PREDICTIVE MODELING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Urbanization has rapidly transformed human settlements into densely populated ecosystems where environmental, social, and infrastructural dynamics interact to influence public health, particularly microbiological safety. The acceleration of urban growth, especially in low- and middle-income countries, has intensified challenges related to microbial contamination in air, water, soil, and food chains, necessitating comprehensive, data-driven understanding and predictive capabilities. This study aims to evaluate the multifactorial effects of urbanization on microbiological safety through an integrated assessment model that incorporates environmental monitoring, spatial analysis, risk classification, and predictive modeling. Drawing on environmental sampling, demographic indicators, GIS-based mapping, and machine-learning-driven forecasting, the research explores how anthropogenic activities, infrastructure density, sanitation systems, climate patterns, and population mobility shape microbial exposure risks in urban settings. Using a mixed-method approach, we analyze microbiological contaminants including pathogenic bacteria, viruses, protozoa, antimicrobial-resistant strains, and bioaerosols across different urban typologies. Results show that rapid, unplanned urbanization significantly increases microbiological hazards due to insufficient sanitation, informal settlements, waste management gaps, climate-driven pollutant redistribution, and intensified human–microbe interactions. The predictive model developed in this research demonstrates high accuracy in forecasting contamination hotspots and future risk trajectories, offering a practical tool for policymakers and urban planners. Our findings reinforce the need for evidence-based urban hygiene regulations, integrated infrastructure reforms, and advanced microbial surveillance systems to mitigate the emerging risks of urban microbiological insecurity. The study contributes a novel interdisciplinary framework for assessing and predicting microbiological safety in rapidly urbanizing regions, supporting sustainable development and population health resilience in the 21st century.